PRIVATIZATION AND THE EFFICIENCY OF THE MANUFACTURING INDUSTRIAL SECTOR (WITH EMPHASIS ON IRAQ - Hoshiar Marouf (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
After decades of poor performance and inefficient operations by state-owned enterprises, governments all over the world earnestly embraced privatization (or conversion the public sector). Thousands of state-owned enterprises (SOEs) have been turned over to the private sector in Africa, Asia, Latin America, and Eastern and Western Europe since the eighties successive programmes of privatizations have been campaigning, particularly, in the developing countries. This operation to all countries was characterized by different contents , processes , conditions and periods of application , but the actual structural relations , in all of its details: the local ,international, social and cultural environments were reflected on the conversion operation in fields of application, levels of momentum, levels of efficiencies and trends of their effects. The experience of Iraq during the late 1980s (and precisely in 1987) and early 1990s (and precisely in1993) is a case of this phenomenon which deserves special attention as the essence of conversion to private sector and its efficiency consequences. Thus, to identify the research’s problem, it has being necessary to reply a basic question which is (if privatization concerned as a more effective solution to the production inefficiency of the public manufacturing sector in the developing countries?). In so far, the researcher concentrated on the following issues:  Privatization and its main conceptual properties.  Privatization and its positive impact on the efficiency of the industrial establishment.  The obstacles that face the positive role of privatization in Manufacturing Industries  Deterioration of the Private Manufacturing Industrial Sector and Privatization Experience in Iraq  Conclusions and recommendations